The association between distal symmetric polyneuropathy in diabetes with all-cause mortality – a meta-analysis - Vági, Orsolya E.; Svébis, Márk M.; Domján, Beatrix A.; Körei, Anna E.; Tesfaye, Solomon; Horváth, Viktor J.; Kempler, Péter; Tabák, Ádám Gy. (Frontiers in Endocrinology, 2023)
Background Distal symmetric polyneuropathy (DSPN) is a common microvascular complication of both type 1 and 2 diabetes with substantial morbidity burden and reduced quality of life. Its association with mortality is equivocal. Purpose To describe the association between DSPN and all-cause mortality in people with diabetes and further stratify by the type of diabetes based on a meta-analysis of published observational studies. Data Sources We searched Medline from inception to May 2021. Study Selection Original data were collected from case-control and cohort studies that reported on diabetes and DSPN status at baseline and all-cause mortality during follow-up. Data Extraction was completed by diabetes specialists with clinical experience in neuropathy assessment. Data Synthesis Data was synthesized using random-effects meta-analysis. The difference between type 1 and 2 diabetes was investigated using meta-regression. Results A total of 31 cohorts (n=155,934 participants, median 27.4% with DSPN at baseline, all-cause mortality 12.3%) were included. Diabetes patients with DSPN had an almost twofold mortality (HR: 1.96, 95%CI: 1.68-2.27, I2 = 91.7%), I2 = 91.7%) compared to those without DSPN that was partly explained by baseline risk factors (adjusted HR: 1.60, 95%CI: 1.37-1.87, I2 = 78.86%). The association was stronger in type 1 compared to type 2 diabetes (HR: 2.22, 95%CI: 1.43-3.45). Findings were robust in sensitivity analyses without significant publication bias. Limitations Not all papers reported multiple adjusted estimates. The definition of DSPN was heterogeneous. Conclusions DSPN is associated with an almost twofold risk of death. If this association is causal, targeted therapy for DSPN could improve life expectancy of diabetic patients.